Controles ambientais na composição florística e na filodiversidade beta em florestas sazonalmente secas do diagonal sul-americano de formações abertas - Danilo Rafael Mesquita Neves (2013)
Studies that may aid the conservation of seasonally dry tropical forests (SDTFs) are urgently needed, since this biome has been highly threatened by anthropic actions. A better understanding of the factors driving the distribution of species across space and through time is critical to support conservation strategies in threatened environments, which therefore justified our reasons to test whether environmental conditions are important factors affecting the floristic and phylogenetic turnover (phylobetadiversity) in SDTFs of the South American Diagonal of Open Formations (Dry Diagonal). Using a database that consisted of 282 SDTFs and 36 environmental variables, we assessed the relative contribution of spatial and environmental factors in explaining the community composition variation and the phylobetadiversity in SDTFs of the Dry Diagonal, applying variance partitioning methods, distance modelling and multivariate analyses. Our results showed that environmental controls, which were previously neglected by other authors, are significant factors affecting both the floristic and the phylogentic turnover in SDTFs. These results point to three main considerations: (1) it is inappropriate to consider the spatial factors as the only drivers of variation in species composition in SDTFs; (2) given the high congruence between floristic turnover and environmental variation in SDTFs, using environmental data to define ecoregions is recommended, until effective floristic lists become available for such purpose; and (3) considering our results of environmental conditions driving the phylobetadiversity, and taking into account a possible scenario of global climatic change, we emphasize the importance of studies that aim to understand the effect of climatic fluctuations in SDTFs.